Matalili-Aga Gahua: Development of the Matalili Framework as a Holistic Model for the Well-Being of the Niue People - Togiamua, Elviso; Eruthayam, Cecily; Lau, Kelvin (SAGE Publications, 2024)
Culturally appropriate research frameworks are needed for investigating Pacific well-being. This study expands on existing Pacific methodologies and presents a well-being research framework by studying the Niue community. Traditional storytelling or talanoa methodology, referred to as tala in the Niue context, was used to explore and understand the lived experiences of well-being from Niue elders. The elders described traditional activities and objects that are required to sustain well-being, as well as relationships with family, community, and the environment. Three interconnected principles that influence the well-being of the Niue people emerged from the tala, namely, Vahā Loto-Agaaga Ofania (Spirit of Care), Fakafetuiaga (Inclusive Relationship), and Fakamalolo (Empowerment). Using a Niue lens, the key three principles were developed into the Matalili-Aga Gahua (Matalili Wellbeing Framework), based on a circular woven pattern that is distinctive to the Niue culture. The principles of the Matalili Wellbeing Framework are proposed as a guide in future Niue-centered research.
Keywords: Niue; Pacific methodology; Pacific-centered research; the Matalili Wellbeing Framework; well-being; Niue; Pacific methodology; Pacific-centered research; the Matalili Wellbeing Framework; well-being; 4203 Health Services and Systems; 42 Health Sciences; 1117 Public Health and Health Services; Public Health; 4206 Public health; Aged; Aged, 80 and over; Female; Humans; Male; Middle Aged; Holistic Health; Pacific Island People; Humans; Holistic Health; Aged; Aged, 80 and over; Middle Aged; Female; Male; Pacific Island People; Aged; Aged, 80 and over; Female; Humans; Male; Middle Aged; Holistic Health; Pacific Island People